Association between vaginal microbiota and risk of early pregnancy miscarriage. (August 2021) - Liu, Xiaorui; Cao, Yunyun; Xie, Xianjing; Qin, Xiaoli; He, Xiaoying; Shi, Chunlei; Zeng, Weihong; Guo, Yuna; Lin, Yi
Highlights: The vaginal community-state types differed significantly among missed miscarriage and normal pregnancy. Vaginal microbiota in patients with missed miscarriage had higher bacterial species richness and diversity. There were lower Lactobacillus levels in vaginal microbiota of patients with missed miscarriage. The phylum Thaumarchaeota is frequently seen in vaginal microbiota of patients with missed miscarriage. Abstract: Approximately 15 % of clinically recognized pregnancies end in miscarriage. To explore the vaginal microbiota profile in women diagnosed with early pregnancy miscarriage (including missed miscarriage [M] or empty-sac miscarriage [E]), the microbial community structure in vaginal fluid was evaluated by Illumina MiSeq sequencing of the 16S rRNA gene V4 region and compared with that in women with normal pregnancy (P). Taxa identified in samples from the P, E, and M groups formed distinct clusters. The M group had the highest bacterial species richness and diversity, with lower Lactobacillus levels and higher Bacteroides, Halomonas, Miscellaneous-Crenarchaeota, Bacillus, Staphylococcus, Escherichia/Shigella, and Acetobacter levels than in the other two groups. The vaginal community-state types differed significantly among the three groups ( P = 0.02) but were similar between the P and E groups ( P = 0.21). Moreover, we identified an optimal marker set composed of 12 operational taxonomic units based on a random forest model that distinguished the M and P groups, with areas under the receiver-operating characteristic curve of 86.76 % and 93.33 % in the training and test groups, respectively. In conclusion, this study highlights that patients with early pregnancy miscarriage had a significantly different vaginal microbiota profile. Microbial markers analyzed by RT-qPCR may be applied for the etiological diagnosis of miscarriage. Further studies should be performed to elucidate the possible mechanism of special strains affecting miscarriage during early pregnancy.